CONTESTING NORMS - Ogundipe, Stephen Toyin (International Library of African Music, 2023)
Contemporary Islamic music in southwestern Nigeria has changed in the last decade and Yoruba Muslim listeners are experiencing music in new ways. This article explores various trends in contemporary Yoruba Islamic music in southwestern Nigeria. The Yoruba are predominantly in southwestern Nigeria and extend to parts of central Nigeria and the West African coast of the Republic of Benin. The article draws on purposefully selected, recorded compositions of Yoruba Islamic artists produced on compact discs between 1979 and 2020, YouTube Videos and in-depth interviews to yield a comprehensive view of the music. It employs Vejlgaard’s (2018) trendspotting theory as a theoretical framework to analyse the texts. It examines the tendencies that shape the re-articulation of religion through the “Muslim sound” and problematises an understanding of the direction of change in contemporary Islamic music. The article argues that contemporary Islamic music in southwestern Nigeria is a product of the quest for Islamic identity and the commodification of musical and social values. This argument puts in context the many dynamics behind the transformations in contemporary Islamic music in Nigeria. Muslim singers draw on the strength of Nigeria’s thriving urban culture industry by adopting production, circulation, and marketing strategies that sustain the commercially successful Nigerian entertainment industry. This development is part of a global reality of social change and modernity transforming Islamic consciousness.
Keywords: Digital media; Commodification; Music; Yoruba (African people); Gospel music; Islamic music; Yoruba Art; Yoruba Muslim; Nigeria; Musical Innovation; Music Trends; African Music